Promoting informed consent in a children's hospital in Tabriz, Iran: a best practice implementation project. (December 2019) - Kabiri, Neda; Hajebrahimi, Sakineh; Alizadeh, Gisoo; Azimzadeh, Solmaz; Farajzadeh, Nayyereh; Talebpour, Amin
ABSTRACT: Introduction: Informed consent is a continuous and dynamic process. It is a crucial part of healthcare procedures that becomes more complex in a pediatric clinical practice, where parents must make decisions for their children. Objectives: The aim of this implementation project was to evaluate the current practice and implement the best practice related to obtaining informed consent in a children's hospital in Tabriz, Iran. Methods: A clinical audit was undertaken using the JBI Practical Application of Clinical Evidence System (JBI PACES) tool. Five audit criteria representing the best-practice recommendations for informed consent were used. A baseline audit was conducted, followed by the implementation of multiple strategies. The project was finalized with a follow-up audit to determine change in practice. Results: The compliance rate of all criteria improved from baseline to follow-up audit. Criteria 1 (obtaining informed consent prior to all nursing procedures) and 5 (provision of information related to the necessity of the treatment) reached 97% compliance in the follow-up cycle. Criterion 4 (provision of information related to the nature and effect of the treatment) achieved 74% compliance. Both criteria 2 and 3 (provision of information related to alternative treatments and consequences of refusing treatment) reached 57% in the follow-up cycle. To improve compliance, meetings were organized with the heads of departments, nurses and residents regarding informed consent. Also, staff were encouraged to report cases where informed consent was not obtained. Conclusion: The audit results indicated an improvement in obtaining informed consent in the included departments. The interventions that were employed can facilitate the implementation of evidence into clinical practice.